Flat and uphill climb time trial performance prediction in elite amateur cyclists - Anton, M. M.; Izquierdo, M.; Ibanez, J.; Asiain, X.; Mendiguchia, J.; Gorostiaga, E. M. (International Journal of Sports Medicine, 2007)
The aim of this study was to determine physiological, anthropometric, biomechanical and hormonal variables related to road flat and uphill climb performance. Eighteen elite level amateur road cyclists (21.1 ± 3.8 yrs), homogeneous with regard to time trial performance (coefficient of variation: 2.9 - 5.2 %), were measured for frontal area (FA), maximal strength, power, cross-sectional area of the quadriceps femoris muscle and basal serum concentrations of total testosterone (TT), free testosterone (FT) and cortisol (C). Maximal (Wmax) and submaximal workload were measured during a progressive discontinuous maximal cycling laboratory test, and two all-out time trial performance tests (duration range: 1049 - 1251 s) were also conducted outdoors on two separate days: a 14-km flat road (average gradient of 0.2 %) and a 6.7-km uphill climb (average gradient of 6 %). Significant negative correlations (p < 0.01 - 0.001) were observed between the individuals' 14-km flat time values and the individual values of Wmax (r = - 0.90) and FA (r = - 0.73). Regression analysis showed that the individual values of the 6.7-km uphill climb trial performance time correlated significantly (p < 0.05 - 0.001) with those of FT (r = - 0.75) and Wmax · kg-1 (r = - 0.66). The present results suggest that flat time trial performance in highly elite amateur cyclists is mainly related to absolute maximal workload and anthropometric variables, whereas uphill climb time trial performance is associated with maximal workload normalized to body mass, as well as with an increased anabolic-androgenic activity.